36 Trans-myocardial extraction of endothelin-1 correlates with increased microvascular resistance following percutaneous coronary intervention. (4th June 2021) - Abraham, George; Nyimanu, Duuamene; Kuc, Rhoda; Maguire, Janet; Davenport, Anthony; Hoole, Stephen
Abstract : Introduction: Coronary microvascular dysfunction (CMD) can persist following successful percutaneous coronary intervention (PCI). Endothelin-1 (ET-1) is a potent vasoconstrictor and may be an important mediator of CMD. We sought to assess the trans-myocardial gradient (TMG – coronary sinus minus coronary root levels) of ET-1 and its precursor - Big ET-1 and assess the correlation with pressure-wire indices of CMD: coronary flow reserve (CFR) and index of microvascular resistance (IMR). Methods: Paired blood samples from the aortic root and coronary sinus were collected before and after pressure wire guided PCI from patients with stable angina. Plasma was then analysed using specific enzyme linked immunosorbent assay (ELISA) for quantification of ET-1 and Big ET-1 and correlated with pressure-wire data. Results: Samples were analysed from 66 patients. Both mean ET-1 and Big ET-1 concentrations increased post-PCI in both the aorta (ET-1: 1.0±0.4 pg/ml to 1.4±0.4 pg/ml, p<0.0001 and Big ET-1: 2.8±1.3 pg/ml to 3.4±1.6 pg/ml, p<0.0001) and coronary sinus (ET-1: 1.0±0.3 pg/ml to 1.2±0.3 pg/ml, p=0.03 and Big ET-1: 3.2±1.7 pg/ml to 3.8±1.5 pg/ml, p=0.01). TMG extraction of ET-1 increased following PCI: 0.05±0.25 pg/ml vs.-0.20±0.41 pg/ml, p=0.01. In contrast, there was TMG release of Big ET-1 before and after PCI: 0.46±1.26 pg/ml vs. 0.38±1.03 pg/ml, p=0.52 ( figure 1 ) . ET-1 extraction correlated with IMR post-PCI (Pearson's r = 0.293, p=0.02, figure 2 ). Patients with CFR<2 post-PCI demonstrated a numerical trend towards higher mean ET-1 extraction than those with preserved CFR post-PCI (0.30±0.51 pg/ml vs. 0.16±0.42 pg/ml, p=0.31) as did those with criteria for Type 4a Myocardial Infarction compared with those without (0.39±0.57 vs. 0.15±0.41, p=0.11). Conclusions: ET-1 and Big ET-1 significantly increase post-PCI. Trans-myocardial extraction of ET-1 increases post-PCI and correlates with post-PCI CMD. Conflict of Interest: none